Rationale and design of the 2 by 2 factorial design GnG-trial: a randomized phase-III study to compare two schedules of gemtuzumab ozogamicin as adjunct to intensive induction therapy and to compare double-blinded intensive postremission therapy with or without glasdegib in older patients with newly diagnosed AML - Sonia Jaramillo (BMC, 2021)
Abstract Background Overall survival remains poor in older patients with acute myeloid leukemia (AML) with less than 10% being alive after 5 years. In recent studies, a significant improvement in event-free, relapse-free and overall survival was shown by adding gemtuzumab ozogamicin (GO), a humanized antibody-drug conjugate directed against CD33, to intensive induction therapy once or in a sequential dosing schedule. Glasdegib, the small-molecule inhibitor of smoothened (SMO), also showed improved overall survival in patients not eligible for intensive chemotherapy when combined with low-dose cytarabine compared to low-dose cytarabine alone. These findings warrant further investigations in the phase III GnG trial. Methods/Design This is a randomized phase III trial with measurable residual disease (MRD) after induction therapy and event-free survival (EFS) as primary endpoints. The two research questions are addressed in a 2 by 2 factorial design. Patients age 60 years and older are upfront randomized 1:1 in one of the two induction arms: GO administered to intensive induction therapy on days 1,4, and 7 versus GO administered once on day 1 (GO-147 versus GO-1), and double-blinded 1:1 in one of the subsequent treatment arms glasdegib vs. placebo as adjunct to consolidation therapy and as single-agent maintenance therapy for six months. Chemotherapy backbone for induction therapy consists of standard 7 + 3 schedule with cytarabine 200 mg/m2 continuously days 1 to 7, daunorubicin 60 mg/m2 days 1, 2, and 3 and high-dose cytarabine (1 g/m2, bi-daily, days 1, 2, and 3) for consolidation therapy. Addressing two primary endpoints, MRD-negativity after induction therapy and event-free survival (EFS), 252 evaluable patients are needed to reject each of the two null hypotheses at a two-sided significance level of 2.5% with a power of at least 85%. Ethics and dissemination Ethical approval and approvals from the local and federal competent authorities were granted. Trial results will be reported via peer-reviewed journals and presented at conferences and scientific meetings. Trial status Protocol version: 1st version 20.10.2020, no amendments yet. Study initiation on February 16, 2021. First patient was recruited on April 1st. Trial registration ClinicalTrials.gov NCT04093505 ; EudraCT 2019-003913-32. Registered on October 30, 2018.